Increase in neutrophil count after repeated exposure of Plasmodium berghei-infected mice to artemisinin - Maslachah, Lilik; Sugihartuti, Rahmi (Universa Medicina, 2017)
Background Leukocytes play an important role in the elimination of malaria infection. The leukocyte profile upon elimination of the malaria parasites that have been exposed to antimalarials and are subsequently capable of faster growth has not been researched. The aim of this research was to evaluate the role of mouse leukocytes in the elimination of parasites as shown by the leukocyte profile.Methods An experimental research with post test only control group design was conducted involving 24 male mice of the Swiss Albino strain weighing 20 g -30 g, and 2.5 months old. They were randomized into four groups: two control groups (K1, KP) and two treatment groups (P1, P4). Artemisinin at a dose of 0.04 mg/g body weight was given to the mice for 3 days, starting 2 days after infection. The leukocyte profile was observed on the 2nd, 5th, 8th, and 10th day after infection. The results were analyzed by two-way Anova.Results As shown in treatment control group KP and treatment group P4, P. berghei that had been passaged in the mice and were still viable after repeated exposure to artemisinin, may cause changes in leukocyte profile. On the 10th day of infection, the neutrophil percentage in group P1 showed a significantly different decrease when compared with the other groups (K1, KP and P4) (p<0.05).Conclusion Repeated exposure to artemisinin of mice infected with P. berghei can cause changes in neutrophil profile in mice.